2002
DOI: 10.1034/j.1399-6576.2002.460806.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune response in asymptomatic smokers

Abstract: Cigarette smokers without chronic obstructive pulmonary disease (COPD) exhibit impaired NK cytotoxic activity in peripheral blood and unbalanced systemic production of pro- and anti-inflammatory cytokines. These changes may serve as predisposing factors for respiratory and systemic infections in the postoperative period and should alert an anesthetist during perioperative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
1
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(126 citation statements)
references
References 27 publications
9
107
1
8
Order By: Relevance
“…Our study shows for the first time that cigarette smoke impairs NK cell-mediated tumor immune surveillance and that altered immunity is associated with increased lung tumor burden in mice. Our study provides experimental evidence that altered immune status may contribute to the increased cancer risk observed in smokers and is in accord with findings that NK cell activity is decreased in smokers (13,14).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Our study shows for the first time that cigarette smoke impairs NK cell-mediated tumor immune surveillance and that altered immunity is associated with increased lung tumor burden in mice. Our study provides experimental evidence that altered immune status may contribute to the increased cancer risk observed in smokers and is in accord with findings that NK cell activity is decreased in smokers (13,14).…”
supporting
confidence: 80%
“…Our findings clearly show that altered NK cell activity is associated with increased tumor burden mice. This is of clinical relevance, because it has been shown that NK cell CTL activity is suppressed in smokers (13,14). Consequently, while it is well-established that carcinogens contained within tobacco smoke lead to cell transformation and cancer formation, we postulate that the effect of cigarette smoke on the immune system further increases the risk for cancer development in smokers.…”
Section: Discussionmentioning
confidence: 93%
“…It was shown that tobacco smoking had a suppressive effect on human immunity as a result of decreased serum concentration of immunoglobulins and lysosyme decreased absolute number of (CD16+) NK-cells and elevated population of (CD8+) T-cytotoxic lymphocytes entailing a decrease in CD4+/CD8+ ratio [33] . Cigarette smokers exhibited impaired NK cytotoxic activity and unbalanced production of pro-and anti-inflammatory cytokines [34] . Smoking could alter immune response either directly through impairment of antigen receptor mediated signal transduction pathways leading to T cell anergy [35] or indirectly through brain immune interactions [36] .…”
Section: Discussionmentioning
confidence: 99%
“…It plays a role in resistance to interferon therapy through immunosuppression of CD4+ and NK cells [41] , by increased hepatic iron load, and by inhibiting the IFN-α-activated signals [42,43] . Most studies found that alcohol decreased the response to interferon-based therapy and this effect is alcohol dosedependent [42][43][44] .…”
Section: Alcohol Abusementioning
confidence: 99%
“…Heavy smoking induces resistance to interferon therapy by suppression of CD4+ and NK activity [41] inducing apoptosis of T-cells [47] , and increasing hepatic iron load [48] . Management: Stop smoking, venesection to reduce iron level, limit diet rich in iron and use of antioxidants as silymarin, vitamin E, betaine, β-carotine, lecithin and selenium.…”
Section: Excessive Smokingmentioning
confidence: 99%